The Use of Military Measures to Counteract Maritime Piracy - Alexander I. KorobeevNatalya А. Knyazeva, Ekaterina A. Knyazeva, (Opción, 2019)
This article studies the option of using naval force as one of the possible methods to counteract maritime piracy via the dialectical method of cognition of phenomena and processes of objective reality. The results of investigations show the effectiveness of using naval measures to counteract piracy as well as the necessity for further cooperation in this direction. In conclusion, to more effectively combat piracy it is necessary to initiate the constant patrolling of hot spots of the world’s oceans by warships through the joint efforts of several states.